A detailed view of the intracellular transcriptome of Listeria monocytogenes in murine macrophages using RNA-seq - Schultze, Tilman; Hilker, Rolf; Mannala, Gopala K.; Gentil, Katrin; Weigel, Markus; Farmani, Neda; Windhorst, Anita C.; Goesmann, Alexander; Chakraborty, Trinad; Hain, Torsten (Frontiers in Microbiology, 2015)
Listeria monocytogenes is a bacterial pathogen and causative agent for the foodborne infection listeriosis, which is mainly a threat for pregnant, elderly, or immunocompromised individuals. Due to its ability to invade and colonize diverse eukaryotic cell types including cells from invertebrates, L. monocytogenes has become a well-established model organism for intracellular growth. Almost 10 years ago, we and others presented the first whole-genome microarray-based intracellular transcriptome of L. monocytogenes. With the advent of newer technologies addressing transcriptomes in greater detail, we revisit this work, and analyze the intracellular transcriptome of L. monocytogenes during growth in murine macrophages using a deep sequencing based approach. We detected 656 differentially expressed genes of which 367 were upregulated during intracellular growth in macrophages compared to extracellular growth in Brain Heart Infusion broth. This study confirmed ∼64% of all regulated genes previously identified by microarray analysis. Many of the regulated genes that were detected in the current study involve transporters for various metals, ions as well as complex sugars such as mannose. We also report changes in antisense transcription, especially upregulations during intracellular bacterial survival. A notable finding was the detection of regulatory changes for a subset of temperate A118-like prophage genes, thereby shedding light on the transcriptional profile of this bacteriophage during intracellular growth. In total, our study provides an updated genome-wide view of the transcriptional landscape of L. monocytogenes during intracellular growth and represents a rich resource for future detailed analysis.